A Solution Proposal to the Interval Fractional Transportation Problem - Guzel, Nuran; Emiroglu, Ybrahim; Tapci, Fatih; Guler, Copkun; Syvry, Mustafa (NATURAL SCIENCES PUBLISHING CORP-NSP, 2012)
In real world applications, frequently may be faced up with the fractional transportation problem that these cost and preference parameters of the fractional objective may not be known in precise manner which are changed in the interval each other. In this study, fractional transportation problem with interval coefficient is transformed to a classical transportation problem by expanding the order 1st Taylor polynomial series with multi variables.
Keywords: Transportation Problem; Linear Fractional Programming; Interval Coefficients; Mathematics; Physics